Development of indigenous biofilm for enhanced biogas production from palm oil mill effluent - Alam, Md. Zahangir; Abdul Hanid, Nurfarhana (Penerbit Akademia Baru, 2017)
Palm oil mill effluent (POME), high content of organic substances can be a great source for production of renewable energy i.e. biogas through microbial biodegradation. The production of biogas has widely been discovered, however, it shows a problem with the low yield of biogas produced. Thus, in order to overcome this problem, a process was used by using indigenous biofilm as a simultaneous pretreatment (hydrolysis) and biogas production. The studies on isolation, purification and screening of biofilm producing bacteria were conducted to evaluate the simultaneous pretreatment and biogas production. The results showed that the developed biofilm enhanced the biogas production with the operating pH, total suspended solid (TSS) and biofilm which were found to be 4-8, 1.5- 4.5 % and 2-4 g respectively. Based on the experiment conducted, the optimum conditions for the biogas production were at pH 8, TSS of 3.0% and biofilm used of 3 g and the highest biogas yield was 382 ml within 5 days of anaerobic digestion. Thus, anaerobic digestion of POME using indigenous biofilm to produce biogas at high yield could be an alternative and effective solution to reduce the source of pollution to the environment.